Integrating Anti-Racism in Health Education - Bisola Olaseni (Inquiry@Queen's Undergraduate Research Conference Proceedings, 2026)
Systemic racism embedded within health education contributes to persistent health inequities, yet anti-racism training remains inconsistently integrated into undergraduate health sciences curricula in North American contexts. In response to identified gaps, Queen’s University developed GLPH 281: Racism and Health in Canada, a semester-long, credit-bearing course co-designed by faculty, students, and teaching assistants and embedded within the Bachelor of Health Sciences program. This study documents the implementation and evaluation of the pilot offering of GLPH 281, with the aim of identifying best practices for sustainable anti-racism education in health sciences. Using a mixed-methods design, students completed pre- and post-course surveys, questionnaires and weekly student feedback. Quantitative data were analyzed using descriptive statistics, while qualitative data underwent iterative and reflexive thematic analysis using NVivo and Microsoft Copilot. Results demonstrate measurable improvements in students’ self-reported confidence and knowledge engaging with racism and health, with composite survey scores increasing across the cohort over the semester. Qualitative analysis further revealed that students highly valued discussion-centered learning, diverse instructional teams, and applied case-based activities, which were perceived as central to creating safe and engaging learning environments. Concurrently, findings identified challenges including content density, an inherent difficulty of meaningfully representing the breadth and diversity of racialized communities in Canada, and some misalignment between assessments and learning objectives, highlighting the constraints in delivering comprehensive anti-racism content within a single course. This study addresses critical gaps in the literature by evaluating a longitudinal, credit-bearing, and collaboratively designed anti-racism course situated within the Canadian socio-historical context. By documenting both outcomes and implementation processes, it offers a replicable and scalable model for integrating anti-racism education into undergraduate health sciences curricula and contributes evidence to support systemic curricular reform toward culturally safe and socially accountable healthcare training.